Industrial Relations Quality and Work Engagement in East Malaysia Private Sector Organizations with Government Involvement as Mediating Factor - Elizabeth Caroline, Augustine (Universiti Malaysia Sarawak (UNIMAS), 2024)
Several scholars claimed that sound industrial relations lead to organizational outcomes. There are studies and instruments to measure sound industrial relations, however, so far based on available databasesthere is no evidence of empirical studies conducted on industrial relations quality and also to assess quality of industrial relations. Thus, this study was conducted to explore and identify elements of sound industrial relations which then were employed as criteria to develop industrial relations quality construct and used to assess the quality of industrial relations. This study also seeks to determine the influence of industrial relations quality on work engagement. The stance of government involvement in industrial relations particularly in Malaysia and its roles in mediating industrial relations and work engagement was also determined in this study. This study employed exploratory sequential design mixed-methodology approach. The qualitative method was used to explore and identify elements of sound industrial relations. The quantitative methods was to determine the criteria to develop industrial relations quality construct and to assess quality of industrial relations, the influence of industrial relations on work engagement, the stance of government involvement in the country’s industrial relations, and to determine the quality of industrial relation particularly in East Malaysia. The study was conducted in unionized private sector organizations in East Malaysia. The informants and respondents for this study are the management officials and union officials. It was initiated by reviewing vast literature on industrial relations best practices both locally and abroad. Data collection of both qualitative and quantitative approaches were conducted online due to the COVID-19 movement control order. In-depth interview sessions with 2 managerial officials and 2 trade union officials were conducted via video conferencing platform on Google Meet. A total of 104 respondents out of 828 sample size responded to the online survey. The qualitative data collected were analyzed using NVivo version 12 plus where text queries were performed to identify the number of references of each industrial relation best practice. There were seven industrial relations practices identified. The seven elements of sound industrial relations identified based on a qualitative approach using NVivo were then determined by employing a quantitative approach using Statistical Package for Social Sciences (SPSS) version 26. Data obtained via qualitative approach and qualitative approach were then triangulated to determine the viability of the seven dimensions identified for developing industrial relations quality construct and criteria to assess the quality of industrial relations. The analysis shows that all seven elements of sound industrial relations can be employed as criteria to develop industrial relations quality construct and also as the criteria to assess the quality of industrial relations. The study also reveals via its findings that government involvement does provide aid to industrial relations in the country. This study provides evidence that the quality of industrial relations in East Malaysia is high and attains the same percentage of achievement as the national IHI.